Strategi Pengembangan Pasar Tradisional sebagai Daya Tarik Wisata di Kota Denpasar Bali: Study Kasus Pasar Kumbasari - Sutrisnawati, Ni Ketut; A.A.A Ribeka Martha Purwahita; I Ketut Saskara; A.A. Sagung Ayu Srikandi Putri; Putu Bagus Wisnu Wardhana (Jurnal Kajian dan Terapan Pariwisata, 2021)
The development of tourism on the island of Bali which is the largest foreign exchange contributor for Indonesia has not been able to provide significant economic benefits for the Balinese people. This can be seen from the increasing number of poor people in Bali covering urban and rural areas from 2012 to 2020, before the tourism sector experienced a significant decline due to the CORONA Virus pandemic. Based on these conditions, it is necessary to develop tourism which prioritizes improving the economy of the local Balinese community by involving local communities directly in tourism development. One of them is by developing traditional markets as a tourist attraction. The reason is because traditional markets are places for buying and selling transactions from all levels of society in Bali. In addition, the development of traditional markets into tourist attractions is expected to be able to compete with the increasing number of modern markets in Bali. The research location chosen is Kumbasari Market which is located in the city of Denpasar. Kumbasari is one of the biggest traditional markets in Bali and currently in the process of renovation. Before the pandemic Covid-19 spread in Bali, Kumbasari was open for 24 hours and became a place to earn a living for hundreds of people of Bali. This development strategy using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). Internal and external factors before renovation analyzed to find various conditions whether it be shortcomings / weaknesses, threats, opportunities and strengths. This can be considered in efforts to improve the quality of the market, so it could be a place worth a visit for both local and foreign tourist so as to provide the maximum benefit for the economic improvement of the people of Bali.